Enhancement of the properties and mesophases stability after the electron beam irradiation on a racemic anti-ferroelectric liquid crystalline mixture. Issue 5 (8th April 2016) - Verma, Rohit; Dabrowski, Roman; Zurowska, Magdalena; Dhar, Ravindra
ABSTRACT: The display parameters and the stability of the various mesophases of a newly synthesised racemic mixture of anti-ferroelectric liquid crystals (AFLCs) have been boosted with the help of the electron beam irradiation. The mixture has phase sequence of isotropic–smectic C–smectic CA crystal. The effective macroscopic polarisation and transition temperatures of the various mesophases of the irradiated mixture have increased as compared with the pure mixture. The macroscopic polarisation of the mixture has increased from 21 to 27 nC/cm 2 due to the irradiation. From various studies, we have observed that the temperature range of the smectic CA phase has increased by 20.6°C with marginal decrease in the temperature range of the smectic C phase. GRAPHICAL ABSTRACT: